PREVALENCE OF FLUOROQUINOLONES RESISTANCE AMONG ESBL-PRODUCING ESCHERICHIA COLI ISOLATED FROM URINE SAMPLES - Ranjan Kumar Sharma; Nitin Gupta; Gurpreet Banga; Aditi Minhas; Rosy Bala; Harit Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Resistance among uropathogens has emerged as a growing concern necessitating re-evaluation of the efficacy of recommended empiric antimicrobial regimens. Misuse and overuse of various antibacterial agents in hospitals are a key cause of the emergence of anti-microbial resistance. The study aimed to identify the prevalence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli from urine specimens and to know the prevalence of Fluoroquinolone resistance among ESBL-producing E. coli isolates. Methods: The study was conducted on 500 E. coli isolates from urine samples received in the Department of Microbiology, MMIMSR, Mullana, Ambala. The organism isolation and identification were done as per the standard procedures and antibiotic sensitivity testing was done following Clinical Laboratory Standard Institute (CLSI) guidelines. All the strains were screened out for ESBL production as per CLSI guidelines. Ciprofloxacin, Norfloxacin, and Ofloxacin discs were used for the detection of fluoroquinolone resistance. Results: Out of the total 500 E. Coli isolates from urine samples received in our laboratory, 69% were found to be ESBL producers. Conclusion: We found a high level of quinolone resistance among ESBL-producing E. coli strains isolated from patients with urinary tract infections. Because of the widespread use of fluoroquinolones in our country, there is a need for sensitive antibiotic stewardship. Further research is needed to ascertain the gravity of quinolone resistance and to swiftly act against its spread among other nosocomial pathogens.